2017
DOI: 10.1186/s12886-017-0562-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal limiting membrane peeling and gas tamponade for myopic foveoschisis: a systematic review and meta-analysis

Abstract: BackgroundMyopic foveoschisis (MF) is among the leading causes of visual loss in high myopia. However, it remains controversial whether internal limiting membrane (ILM) peeling or gas tamponade is necessary treatment option for MF.MethodsPubMed, EMBASE, CBM, CNKI, WANFANG DATA and VIP databases were systematically reviewed. Outcome indicators were myopic foveoschisis resolution rate, visual acuity improvement and postoperative complications.ResultsNine studies that included 239 eyes were selected. The proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…Our results demonstrate that, for the treatment of myopic foveoschisis (MF), vitrectomy without internal limiting membrane peeling (ILMP) has similar outcomes to vitrectomy with ILMP. This is consistent with previous reports [4,11]. Indeed, within-cohort statistical analysis showed that significant visual improvement was only achieved in the no-ILMP cohort.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrate that, for the treatment of myopic foveoschisis (MF), vitrectomy without internal limiting membrane peeling (ILMP) has similar outcomes to vitrectomy with ILMP. This is consistent with previous reports [4,11]. Indeed, within-cohort statistical analysis showed that significant visual improvement was only achieved in the no-ILMP cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Myopic foveoschisis (MF) was first described by Takano and Kishi in 1999, and is recognized as one of the major complications associated with pathological myopia [1,2]. Many subsequent studies have demonstrated that vitrectomy with internal limiting membrane peeling (ILMP) can be effective in producing both anatomical and functional improvement in MF [3][4][5][6][7]. In order to reduce postoperative macular hole (MH) formation and foveal damage, a partial ILMP technique with foveal sparing was proposed [8], but there is little evidence that this technique has better outcomes than complete ILMP [9,10] Furthermore, more recent studies have shown similar anatomical and functional improvements can be achieved without any form of IMLP [4,11], casting doubt on the benefits of ILMP.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a meta-analysis [13] reported that gas tamponade might cause more complications compared to vitrectomy without tamponade, although no significant differences were found in the outcomes of visual acuity or in the resolution of myopic foveoschisis. Another report [14] demonstrated a high myopic foveoschisis resolution rate (88%) with intraocular air tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study showed that the chance of successful resolution was similar between the group with gas tamponade and that without gas tamponade [51]. Indeed, a meta-analysis showed that for eyes undergoing vitrectomy for myopic foveoschisis, gas tamponade did not have significant impact on visual acuity or the rate of resolution of foveoschisis, yet it was associated with more complications [42]. Several studies also reported the paradoxical occurrence of FTHM from the use of gas tamponade, which could squeeze SRF within the limited space through the weak point of fovea [52][53][54].…”
Section: Gas Tamponadementioning
confidence: 95%
“…For myopic foveoschisis, ILM peeling helps to ensure that all tractional forces from premacular glial cells and vitreous cortex are completely removed [42]. It increases retinal compliance and allows the retina to better conform to the posterior staphyloma [42].…”
Section: Myopic Foveoschisismentioning
confidence: 99%